2010
DOI: 10.4319/lo.2010.55.6.2597
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between limiting nutrients: Consequences for somatic and population growth of Daphnia magna

Abstract: To assess the significance of nutrient interactions on animal performance, life-history experiments were conducted with the freshwater herbivore Daphnia magna in a system with two limiting nutrients (i.e., sterols and polyunsaturated fatty acids [PUFAs]). By experimentally increasing the availability of dietary cholesterol either in the absence or in the presence of different dietary PUFAs we investigated whether dietary PUFAs differ in their potential to affect the sterol-limited growth kinetics of the herbiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 46 publications
2
87
2
Order By: Relevance
“…The tendency of DHA to accumulate in winter-active poikilotherms suggests that this PUFA plays a crucial role in the adaptation to low temperatures (Hazel and Williams 1990;Smyntek et al 2008). However, as dietary DHA is effectively converted to EPA in Daphnia (von Elert 2002;Martin-Creuzburg et al 2010), the positive effect of DHA supplementation on population growth rates is presumably the result of an increased availability of EPA.…”
Section: Discussionmentioning
confidence: 98%
“…The tendency of DHA to accumulate in winter-active poikilotherms suggests that this PUFA plays a crucial role in the adaptation to low temperatures (Hazel and Williams 1990;Smyntek et al 2008). However, as dietary DHA is effectively converted to EPA in Daphnia (von Elert 2002;Martin-Creuzburg et al 2010), the positive effect of DHA supplementation on population growth rates is presumably the result of an increased availability of EPA.…”
Section: Discussionmentioning
confidence: 98%
“…attenuates the decline in body P content under P‐limiting conditions. Recent laboratory studies showed the colimitation of herbivore growth by P and PUFA (Becker & Boersma 2003) or sterols and PUFA (Martin‐Creuzburg, Sperfeld & Wacker 2009; Martin‐Creuzburg, Wacker & Basen 2010), but data on organism’s stoichiometry are lacking. Sterols are essential food components for herbivorous arthropods (Behmer & Nes 2003; Von Elert, Martin‐Creuzburg & Le Coz 2003), which have to metabolize dietary phytosterols into cholesterol (Svoboda & Thompson 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The sterols were analyzed by gas chromatography (GC) using a HP 6890 gas chromatograph (Agilent Technologies, Santa Clara, CA, USA) equipped with a flame ionization detector (FID) and a HP‐5 capillary column (Agilent Technologies). Details of the GC settings are given elsewhere . The sterols were quantified by comparison with the internal standard 5α‐cholestane using multipoint calibration curves generated for different sterols.…”
Section: Methodsmentioning
confidence: 99%